The Wind Employment in Spain (1995-2010): A Theoretical Approximation Applied to the Region of Galicia - Regueiro Ferreira, Rosa Maria; Doldán Garcia, Xoan Ramón (International Journal of Energy Economics and Policy, 2012)
The development of the renewable energies, and especially of the wind power, in the last decades has stayed out of any discussion. The advantages associated with the energy of the odd wind have considered in occasions authentic information that they them should corroborate. For example, about the streghness of creating jobs, there do not exist official statistics that gather the dimension of the created employment, without forgetting that the field of the energy stands out for being intensive in the capital. In this paper, there is realized an analysis of the different bibliographical sources relative to the generation of employment in the wind sector in Spain, establishing a few margins of the creation of the same one for categories for the region of Galicia, in the period (1995-2010). Keywords: Renewable energy; wind energy; wind promotors JEL Classifications: Q25; Q43; 013